Transformation of face transplants: volumetric and morphologic graft changes resemble aging after aacial allotransplantation - Kückelhaus, Maximilian; Turk, M.; Kumamaru, K. K.; Wo, L.; Bueno, E. M.; Lian, C. G.; Alhefzi, M.; Aycart, M. A.; Fischer, Sebastian; Girolami, U. De; Murphy, G. F.; Rybicki, F. J.; et al. (American journal of transplantation, 2016)
Facial allotransplantation restores normal anatomy to severely disfigured faces. Although >30 such operations performed worldwide have yielded promising short-term results, data on long-term outcomes remain scarce. Three full-face transplant recipients were followed for 40 months. Severe changes in volume and composition of the facial allografts were noted. Data from computed tomography performed 6, 18 and 36 months after transplantation were processed to separate allograft from recipient tissues and further into bone, fat and nonfat soft tissues. Skin and muscle biopsies underwent diagnostic evaluation. All three facial allografts sustained significant volume loss (mean 19.55%) between 6 and 36 months after transplant. Bone and nonfat soft tissue volumes decreased significantly over time (17.22% between months 6 and 18 and 25.56% between months 6 and 36, respectively), whereas fat did not. Histological evaluations showed atrophy of muscle fibers. Volumetric and morphometric changes in facial allografts have not been reported previously. The transformation of facial allografts in this study resembled aging through volume loss but differed substantially from regular aging. These findings have implications for risk-benefit assessment, donor selection and measures counteracting muscle and bone atrophy. Superior long-term outcomes of facial allotransplantation will be crucial to advance toward future clinical routine.